Амфора з Чортомлика та пектораль з Товстої Могили: загальне та особливе (історіографічний огляд і нові спостереження) - Бабенко, Л.І. (Археологія і давня історія України, 2021)
У статті проведено історіографічний огляд
робіт, присвячених співставленню двох шедеврів
греко-скіфської торевтики — срібної амфори з Чортомлика та золотої пекторалі з Товстої Могили,
а також репрезентовано декілька нових спостережень з цієї проблеми. The comparison of the masterpieces of the Greek-
Scythian toreutics — the silver amphora from Chortomlyk
and the gold Pectoral from Tovsta Mohyla became
the set tradition from the moment of the pectoral
discovery. Both objects have a range of distinct common
traits, such as composition tripartite structure
with plot identical in contents — scenes of nomadic
daily routine, represented by miniature high relief figures
of the characters, scenes of animal combat, and
also the zones of floral ornament, enlivened by birds’
figures and many other nuances.
The researchers compared the amphora and the
pectoral in different contexts. A. P. Mantsevich saw
in them, first of all, handiwork of Thracian craftsmen.
Many researchers interpreted the compositions of amphora
and pectoral as reflection of cosmogonic idea
about tripartite Universe structure where the scenes
of animal combat were associated with the day of vernal
equinox and the idea of the cyclicality of seasons,
the floral composition — with the World Tree symbolic,
and the horse riding — with ritualistic sacrifice
during a coronation or burial of king (E. E. Kuzmina,
B. M. Mozolevskyi, D. S. Raevskii).
Ann Farkas interpreted the plots on amphora and
pectoral as cosmogonic act of creation, S. S. Bessonova
saw in them the elements of cattle-breeding rituals,
connected with calendar holidays. D. A. Machinski associated
both handiworks with the cult of the Great
Goddess, and F. R. Balonov considered the amphora
and the pectoral compositions the model of mythopoetic
space — the time.
The researchers also didn’t reach common ground
on the handiwork authorship — part of them consider
the amphora and pectoral originated from the one
workshop (W. Rudolph, D. Williams, F. R. Balonov),
and some believed that both objects origin from different
workshops (E. A. Savostina).
Several more observations can be added to this similarity
— in the context of using some or other beverages
in the represented rituals, the compositional nuances
of the ornithomorhic bestiary, numeric symbolism,
etc. So, the comparison of two masterpieces in different
contexts remains a promising direction of their
study.